A Taxonomic Revision of Nearctic Conostigmus (Hymenoptera: Ceraphronoidea: Megaspilidae) - Trietsch, Carolyn; Mikó, István; Ezray, Briana; Deans, Andrew R. (Zootaxa, 2020)
We revise the species of Conostigmus Dahlbom, 1858 (Hymenoptera: Ceraphronoidea: Megaspilidae) found in North America, north of Mexico. We describe the following 12 new species: Conostigmus dessarti Trietsch & Mikó sp. nov.; C. duncani Trietsch sp. nov.; C. franzinii Trietsch & Mikó sp. nov.; C. johnsoni Trietsch & Mikó sp. nov.; C. lepus Trietsch sp. nov.; C. longiharpes Trietsch sp. nov.; C. michaeli Trietsch sp. nov.; C. minimus Trietsch & Mikó sp. nov.; C. muratorei Trietsch sp. nov.; C. musettiae Trietsch & Mikó sp. nov.; C. rosemaryae Trietsch sp. nov.; and C. washburni Trietsch sp. nov. We also redescribe the following 12 species: Conostigmus abdominalis (Boheman, 1832); C. bipunctatus Kieffer, 1907; C. dimidiatus (Thomson, 1858); C. erythrothorax (Ashmead, 1893); C. laeviceps (Ashmead, 1893); C. muesebecki Dessart & Masner, 1965; C. nigrorufus Dessart, 1997; C. obscurus (Thomson, 1858); C. orcasensis (Brues, 1909); C. pulchellus Whittaker, 1930; C. quadratogenalis Dessart & Cooper, 1975; and C. triangularis (Thomson, 1858). We report specimens of C. abdominalis (Boheman, 1832) and C. bipunctatus Kieffer, 1907 from the Nearctic for the first time, expanding the range from Palearctic to Holarctic for both species. We regard the following 19 species as having uncertain status due to reasons such as missing type specimens: Conostigmus ambiguus (Ashmead, 1893); C. bacilliger (Kieffer, 1906); C. bakeri Kieffer, 1908; C. californicus (Ashmead, 1893); C. canadensis (Ashmead,1888); C. crawfordi (Mann, 1920); C. harringtoni (Ashmead, 1888); C. hyalinipennis (Ashmead, 1887); C. inermis (Kieffer, 1906); C. integriceps (Kieffer, 1906); C. marylandicus (Ashmead, 1893); C. nevadensis (Kieffer, 1906); C. nigripes (Kieffer, 1906); C. ottawensis (Ashmead, 1888); C. pergandei (Ashmead, 1893); C. popenoei (Ashmead, 1893); C. rufoniger (Provancher, 1888); C. schwarzi (Ashmead, 1893); and C. trapezoidus Kieffer, 1908. We transfer Conostigmus arietinus (Provancher, 1887) to Dendrocerus Ratzeburg, 1852, and consider Conostigmus subinermis (Kieffer, 1907) to be absent from the Nearctic and limited to the Palearctic. The Nearctic species C. timberlakei Kamal, 1926 remains incertae sedis. We provide the name Conostigmus fulgidus Mikό and Trietsch to replace the junior homonym Conostigmus lucidus Mikό and Trietsch 2016. We provide a key for the identification of Nearctic Conostigmus species, and provide comments on their natural history. Finally, we infer evolutionary relationships within Megaspilinae using male genitalia and other morphological characters. This work represents the first in-depth study and revision of Conostigmus in North America, and contributes the first annotated identification key to Nearctic Conostigmus species.